No mutations found in exon 2 of gene p16CDKN2A during rat tongue carcinogenesis induced by 4-nitroquinoline-1-oxide - Minicucci, Eliana Maria [UNESP]; da Silva, Glenda Nicioli [UNESP]; Ribeiro, Daniel Araki; Salvadori, Daisy Maria Favero [UNESP] (Springer, 2009)
The medium-term tongue carcinogenesis assay is a useful model for studying oral squamous cell carcinomas phase by phase. The present study aimed to investigate mutations in exon 2 of gene p16CDKN2A during rat tongue carcinogenesis induced by 4-nitroquinoline 1-oxide (4NQO) using direct DNA-sequencing method. A total of 30 male Wistar rats were treated with 4-nitroquinoline 1-oxide (4NQO) in drinking water for 4, 12, and 20 weeks at 50 ppm dose. Ten animals were used as negative control. No histopathological changes in tongue epithelia were observed among controls or in the group treated for 4 weeks with 4NQO. Following 12-week treatment, hyperplasia and epithelial dysplasia were found in mild and moderate forms. At 20 weeks, the tongue presented moderate and/or severe oral dysplasia and squamous cell carcinoma, with squamous cell carcinoma in the majority of animals. No mutations were found in any experimental period evaluated that corresponded to normal oral mucosa, hyperplasia, dysplasia and squamous cell carcinomas. Taken together, our results suggest that p16CDKN2A mutations in exon 2 are not involved in the multistep tongue carcinogenesis of Wistar rats induced by 4NQO.
Keywords: p16; Rat tongue mucosa; Oral squamous cell carcinoma; 4-Nitroquinoline 1-oxide; Direct DNA-sequencing